Developing the humanitarian logistics network of Bohol province for disaster response operations - Nasam, Michelle Garcia- (School of Urban and Regional Planning, University of the Philippines Diliman, 2019)
When a disaster strikes, an adequate and timely response is critical to alleviate casualties and reduce health impacts.The first 72 hours post-disaster is considered the most critical time for any relief effort, as chances for survival without any food and water decrease significantly after this time period. Hence, the challenge is how to deliver the appropriate emergency supplies in the right quantities, exactly where and when these are needed. Foremost, the goal of typical response operations is to have critical services reach as many affected people in the shortest possible time, even at the expense operational-and cost-efficiency. However, with logistics accounting for 60-80% of response coast, there is much room for operations improvement. Increasing prices of fuel, coupled with a lack of coordination amongst government units, and an ad hoc assessment system add to this high logistics coast, which in turn reduces distribution of resources. Some humanitarian organizations (HO's) even state that a dollar spent in preparedness is worth seven dollars in response (Jahre, Ergun and Goentzel 2015). To help address theses issues, the research recommends the use of a physical distribution network composed of entry ports, main distribution hubs, local distribution centers, and the shortest land-based routes to link them. The result is a multi-level distribution and routing logistics model, tested against network failure and standard response time. In this model, emergency supplies are first received in permanent depots, and then shipped to temporary local distribution centers to be picked-up by the affected population. Using the island province of Bohol as a case study, this research contributes to the understanding of the relationships among vulnerability assessment, supply chain management, and a systematic needs assessment. The research anchors on two main premises: the humanitarian distribution network can capitalize on commercial supply chain management (SCM), and that vulnerability assessment is vital for physical network continuity. First, the research examines existing commercial supply chain models to determine network designs most applicable applicable to humanitarian logistics.These design guidelines are then validated against the existing logistics network of the study area. As part of the network's vulnerability assessment, the study area's natural hazards are interlaid with its existing physical and socio-economic context to visualize and analyze relationships between natural hazards, supply and distributions facilities, transport networks, and population distribution. The research concludes by providing general recommendations on how the logistics plan can be integrated into existing planning frameworks, especially in DRRM provisions in the Comprehensive Land Use Plan and Physical Development Plan. Considering that the Philippines is archipelagic in nature, a logistics study on an island province can then be duplicated to other similar areas.